Cultural Lens on Servant Leadership: Fostering Green Awareness and Environmental Protection at Heritage Site - Prasetya, Agustian Budi; Pratama, Iqbal Reza; Alimi, Moh Yasir (Komunitas: International Journal of Indonesian Society and Culture, 2024)
The Pesanggrahan Dalem Paku Buwono IX (PB IX) is situated in Langenharjo Village, Sukoharjo Regency, Indonesia. The site was founded in 1870 by PB IX (1830-1893), but it is currently facing environmental degradation, despite its past pristine water and natural hot springs. However, with the new management takeover by GPH Wicaksono, a descendant of the Surakarta Royal Family, there is hope for the conservation of this heritage site. This research explores servant leadership practices within the cultural context of GPH Wicaksono as the manager of heritage site in Langenharjo village. Drawing on Greenleaf's servant leadership principles, it examines how Javanese culture, and the wisdom of the manager can foster collective engagement in environmental preservation. The study aimed to provide valuable insights into leadership's role in promoting sustainability for the heritage site and the local community. The identification of servant leadership implementation in the heritage site was using a qualitative approach. Data collection involves on-site observations and in-depth interviews with relevant stakeholders, including community leaders, members of the community, and cultural enthusiasts. The data is analyzed using phenomenology analysis to identify specific servant leadership behaviors of site manager and their role in fostering environmental preservation and sustainability within the community. The study's findings showed that the manager is dedicated to preserving the heritage site by promoting strong ties with Javanese culture and tradition. He encourages an eco-friendly mindset and collective participation to sustainably protect the environment. He also values effective communication and respects his colleagues, which in turn fosters trust and empowerment among the team. By following principles of Javanese culture, he leads and empowers communities toward environmental sustainability. This study contributes to the importance of incorporating cultural values in leadership practices to foster collective engagement and green awareness for long-term environmental preservation. It serves as an initial study for further research using quantitative analysis to deepen our understanding of servant leadership’s effectiveness in diverse cultural contexts.